Predicting Blue-Green-Grey Space Changes in Chittagong City Corporation Area Based On CA-Markov Model - Shamsunnaher; Saika, Ummeh (The Jahangirnagar Review, 2025)
Using remote sensing and a Geographic Information System (GIS), this study examines the land use change in the Chittagong city corporation region from 2000 to 2020. It then uses a Cellular Automata Markov model to forecast the likelihood of future land use patterns for 2030.In this study, land use classification is defined as follows: Blue represents water bodies, Green indicates vegetation cover, and Grey signifies built-up areas and there is another category the other open spaces, those are classified using the maximum likelihood supervised classification. Three sets of multi-temporal Landsat images taken in 2000, 2010 and 2020, where one image from the Landsat 8 Operational Land Imager (OLI) and two from the Landsat 5 Thematic Mapper (TM). The analysis revealed that from 2000 to 2020 Built up area and vegetation cover increased respectively 13% and 6% where other open spaces and water body decreases 18% and 1% respectively.